Genomic insights into a clinical Salmonella Typhimurium isolate carrying plasmid-mediated blaNDM-5 - Fan Huang; Genglin Guo; Lu Feng; Tongbo Cai; Xu Huang (Journal of Global Antimicrobial Resistance)
Objective: Highly carbapenem-resistant Salmonella has emerged worldwide in recent years and is largely associated with the multiform transmission of resistance genes, which poses a huge challenge in clinical practice. Our study delves into the resistance mechanisms and epidemiology of blaNDM-carrying plasmids. Methods: Whole-genome sequencing was utilised to analyse the molecular characteristics and antimicrobial resistance mechanisms of Salmonella isolates recovered from the faeces of a paediatric patient at the Children's Hospital of Nanjing Medical University. Moreover, we conducted an epidemiologic analysis and focused on studying the mechanisms of plasmid-mediated blaNDM transmission, incorporating genomes deposited in the NCBI Pathogen Detection database. Results: The clinical isolate 23S9 belonged to serovar Typhimurium, antigenic profile 4:i:-, ST34, and carried pNDM_23S9 harbouring several antimicrobial resistance genes, including aac(6′)-Ib-cr6, OXA-1, catB3, arr-3, qacEdeltal and blaNDM. Comparative analysis revealed that blaNDM-5 can exist in different plasmids of different isolates, proving its transmission through plasmids. Furthermore, blaNDM-carrying isolates are mostly resistant to beta-lactams, aminoglycosides, sulphonamide, macrolides, and trimethoprim. Conclusions: These findings provided thorough and intuitive insights into the intercontinental spread of blaNDM-carrying Salmonella. Ongoing surveillance is essential for effectively monitoring the worldwide dissemination of this high-risk carbapenem-resistant Salmonella.